Wall-to-horizontal diaphragm connections in historical buildings: A state-of-the-art review. (15th November 2019) - Solarino, Fabio; Oliveira, Daniel V.; Giresini, Linda
Highlights: Effective URM wall-to-horizontal diaphragm connections prevent seismic mechanisms. Experimentally calibrated connection models should be developed and used. Steel anchors enhance the PO and shear behavior effectively. Global FEM or EF seismic analyses usually neglect nonlinear connection behavior. Nonlinear kinematic and rocking models are useful for the local seismic assessment. Abstract: Wall-to-horizontal diaphragm connections play a crucial role in the global stability of historical buildings under seismic actions. When these links are ineffective or absent, engineered measures should be considered to enhance the earthquake-resistant box-type behavior. Besides the great variety on the construction systems and materials, common damages were observed in recent seismic events showing the high vulnerability of local mechanisms promoted by the lack of structural integrity. Although the acknowledged importance of connections, this topic has been practically neglected over time among the research community and practitioners and only few of them focused on the influence of diaphragm-to-wall connections on the dynamic behavior of the building as a whole. This paper presents a literature review of the traditional wall-to-floor or wall-to-roof connections in unreinforced masonry buildings and summarizes typical and innovative strengthening solutions, taking into account the indications provided by the few design codes addressing this topic. Experimental laboratory researches are investigated, including shaking table tests on global and local scale, and cyclic or monotonic tests to characterize anchoring systems. An overview of the typical vulnerability assessment approaches and modelling techniques is given, considering present standards that account for connections.